2007
DOI: 10.1016/j.jacc.2007.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intracoronary Cell Therapy on Left Ventricular Function in the Setting of Acute Myocardial Infarction

Abstract: Intracoronary cell therapy following percutaneous coronary intervention for AMI appears to provide statistically and clinically relevant benefits on cardiac function and remodeling. These data confirm the beneficial impact of this novel therapy and support further multicenter randomized trials targeted to address the impact of intracoronary cell therapy on overall and event-free long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
325
1
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 479 publications
(345 citation statements)
references
References 27 publications
13
325
1
6
Order By: Relevance
“…There were less reinfarctions, death, or HF hospitalizations in cell treated groups. 13 The EF increase is modest, sometimes transient, and less than expected compared to animal models (Figs. 1a and b).…”
Section: Timing Comparisonsmentioning
confidence: 86%
See 4 more Smart Citations
“…There were less reinfarctions, death, or HF hospitalizations in cell treated groups. 13 The EF increase is modest, sometimes transient, and less than expected compared to animal models (Figs. 1a and b).…”
Section: Timing Comparisonsmentioning
confidence: 86%
“…61,80 Landmark, large-scale trials using BMC showed benefits in neovascularization, ventricular function and remodeling. [12][13][14] The ACT-34 study demonstrated that EPC mobilization, isolation and injection significantly improved recurrent angina. 81 One-year results from the largest trial using allogeneic MSC post-AMI showed ventricular benefit, with significant decreases in HF and re-hospitalizations in the treated group.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
See 3 more Smart Citations